Prevalence and Prevention of Diarrhoea among Infants in Rural Areas of Ekiti State, Nigeria - Owoseni Joseph Sina; Muhammad Nadir Shahzad; Asim Muneeb Khan; Mazhar Hussain Bhutta; Beenish Ambereen (Indian Journal of Forensic Medicine & Toxicology, 2021)
In Nigeria, diarrhoea has emerged as one of the common causes of gastroenteritis in children and adultpopulation. Generally speaking, it is a condition in which three or more liquid or loose bowel movement perday happen. Basically, prevalence of diarrhoea as a disease is highly caused due to poor sewerage disposal,hygiene conditions and contaminated water at the household level. This study sought to investigate theprevalence and prevention of diarrhoea among infants in Ekiti State, Nigeria. The survey research designwas used to accomplish this study. Among the rural population of the area, a sample of one hundred (N=100)mothers were selected randomly to gather information for the study. The primary data was collected by usingthe questionnaire and secondary data was collected from textbooks, research journals/articles published onthe subject in the past. The findings shown, that the potential causes and prevention mechanisms of diarrhoeaamong children (less than 5 years) in the study area are not known to most of the nursing mothers. Therefore,it is imperative to engage community and women in particular aimed to ensure the success of educationalinterventions.